The Role of Different Tourism Concepts and Forms in the Pursuance of Sustainable Development Goal - Niezgoda, Agnieszka (Turyzm/Tourism, 2008)
The article presents the concept of sustainable development, underlining the interrelations between ecological, economic and social goals that provide its foundation. Against this background it discusses the role of tourism in the realization of sustainable development objectives by referring to the various forms of tourism development described in the literature. The concepts of soft tourism, green tourism, agrotourism, and - in particular - alterative tourism and ecotourism, are presented as forms compatible with the goals of sustainable development. Special attention is given to alterative tourism and mass tourism in terms of their coexistence or mutual exclusion in the light of qualitative and quantitative characteristics of forms of mass tourism. The article concludes with a presentation of the concept of sustainable tourism.